The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1097/md.0000000000026999
|View full text |Cite
|
Sign up to set email alerts
|

The neuromuscular and multisystem features of RYR1-related malignant hyperthermia and rhabdomyolysis

Abstract: Introduction: Malignant hyperthermia (MH) and exertional rhabdomyolysis (ERM) have long been considered episodic phenotypes occurring in response to external triggers in otherwise healthy individuals with variants in RYR1. However, recent studies have demonstrated a clinical and histopathological continuum between patients with RYR1-related congenital myopathies and those with ERM or MH susceptibility. Furthermore, animal studies have shown non-neuromuscular features such as a mild bleeding disorder and an imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 45 publications
(102 reference statements)
0
15
0
Order By: Relevance
“…6. Personal history of an RYR1 variant detected on diagnostic testing in the neuromuscular clinic for symptoms suggestive of a neuromuscular disorder but without a specific clinical or histopathologic diagnosis and/or fulfilling one of the other referral criteria; these are often coincidentally found RYR1 variants; frequent reasons for RYR1 sequencing in the neuromuscular clinic are myalgia, muscle cramps, and muscle weakness 18,19…”
Section: Methodsmentioning
confidence: 99%
“…6. Personal history of an RYR1 variant detected on diagnostic testing in the neuromuscular clinic for symptoms suggestive of a neuromuscular disorder but without a specific clinical or histopathologic diagnosis and/or fulfilling one of the other referral criteria; these are often coincidentally found RYR1 variants; frequent reasons for RYR1 sequencing in the neuromuscular clinic are myalgia, muscle cramps, and muscle weakness 18,19…”
Section: Methodsmentioning
confidence: 99%
“…The study protocol of the parent project has already been published. 16 Study procedures relevant for this report are reported in Part 1 ‘questionnaire studies’ and Part 2: ‘Clinical studies’. After the publication of the study protocol, 16 an amendment was made to the study design.…”
Section: Methodsmentioning
confidence: 99%
“… 16 Study procedures relevant for this report are reported in Part 1 ‘questionnaire studies’ and Part 2: ‘Clinical studies’. After the publication of the study protocol, 16 an amendment was made to the study design. The standardized history of neuromuscular symptoms questionnaire (see ‘Study procedures’), was filled out by patients and healthy controls because there are no validated questionnaires available on neuromuscular symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Rare disease-causing mutations are associated with a small but significant subset (∼15%) of RM patients. Environmental factors such as viral infections (SARS-CoV-2, HIV), physical exertion, certain medications and drugs are major contributing factors in combination with a genetic predisposition (East, Alivizatos, Grundy, Jones, & Farmer, 1988; Knoblauch, Dagnino-Acosta, & Hamilton, 2013; Rawson, Clarkson, & Tarnopolsky, 2017; Szugye, 2020; van den Bersselaar et al, 2021; Wu, Wong, Cheng, & Yu, 2022). Even in genetic forms of RM, environmental factors increase the susceptibility to recurrent episodes of muscle breakdown (Kruijt et al, 2021).…”
Section: Introductionmentioning
confidence: 99%